2018
DOI: 10.1021/acs.jpcc.8b01045
|View full text |Cite
|
Sign up to set email alerts
|

How SnF2 Impacts the Material Properties of Lead-Free Tin Perovskites

Abstract: Lead-based halide perovskites (APbX3) are fascinating optoelectronic materials. Because of toxicity issues of Pb, Sn-based halide perovskites are studied, although less so, as an alternative. Adding SnF2 often improves the properties of Sn halide perovskite-based devices. This effect is usually ascribed to suppression of Sn2+ → Sn4+ oxidation and/or decreased Sn vacancy concentration. These effects will change the doping, sometimes in opposite directions. Here we review the effect of addition of SnF2 during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
225
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(237 citation statements)
references
References 67 publications
(143 reference statements)
6
225
0
6
Order By: Relevance
“…To overcome the Sn oxidation issue, a widely adopted strategy is adding SnF 2 to SnI 2 precursor solutions. The critical role of the SnF 2 addition has been confirmed by later studies and reviewed recently by Gupta et al [66] More recently, formamidinium tin iodide (FASnI 3 ) was introduced to replace MASnI 3 due to improved film morphology and electrical properties and has been gradually become the most popular choice for Sn perovskite solar cells. [65] They found that the SnF 2 addition reduced the carrier density from ≈10 19 to ≈10 17 cm −3 and, more importantly, suggested that the reduced carrier density was due to the increase in the Sn chemical potential, and thus, an increase in the formation energy of V Sn (Figure 6f) and a reduction in V Sn concentration.…”
Section: Wwwadvmatde Wwwadvancedsciencenewscommentioning
confidence: 86%
“…To overcome the Sn oxidation issue, a widely adopted strategy is adding SnF 2 to SnI 2 precursor solutions. The critical role of the SnF 2 addition has been confirmed by later studies and reviewed recently by Gupta et al [66] More recently, formamidinium tin iodide (FASnI 3 ) was introduced to replace MASnI 3 due to improved film morphology and electrical properties and has been gradually become the most popular choice for Sn perovskite solar cells. [65] They found that the SnF 2 addition reduced the carrier density from ≈10 19 to ≈10 17 cm −3 and, more importantly, suggested that the reduced carrier density was due to the increase in the Sn chemical potential, and thus, an increase in the formation energy of V Sn (Figure 6f) and a reduction in V Sn concentration.…”
Section: Wwwadvmatde Wwwadvancedsciencenewscommentioning
confidence: 86%
“…The larger V oc loss of low‐bandgap mixed Pb–Sn PSCs is likely associated with two factors: 1) the high trap density of the perovskite film, resulting in severe nonradiative recombination, and 2) an unsuitable energy‐level alignment between perovskite film and charge transport layers . It is believed that the Sn 4+ acts as p‐type dopants in the Pb–Sn‐alloyed perovskite films which induce deep trap states to boost nonradiative recombination . Unfortunately, even a highly purified commercial starting material SnI 2 (99.9%, trace metal) could contain up to 10 wt% of SnI 4 due to the technical difficulty of the complete removal of Sn 4+ during the synthesis, as reported by Wakamiya and coworkers recently .…”
mentioning
confidence: 99%
“…[15,27,[29][30][31] It is believed that the Sn 4þ acts as p-type dopants in the Pb-Sn-alloyed perovskite films which induce deep trap states to boost nonradiative recombination. [32][33][34] Unfortunately, even a highly purified commercial starting material SnI 2 (99.9%, trace metal) could contain up to 10 wt% of SnI 4 due to the technical difficulty of the complete removal of Sn 4þ during the synthesis, as reported by Wakamiya and coworkers recently. [35] In addition, even though the storage of the starting material SnI 2 and the preparation of Sn-based perovskite films is carried out under a N 2 -filled glove box, it is impossible to completely prevent oxygen exposure, so a certain degree of oxidation of Sn 2þ to Sn 4þ is still likely to occur during that time.Therefore, in this work, we reported an in situ Sn 4þ reduction method by adding excess Sn powder into the formamidinium tin iodide (FASnI 3 ) precursor solution during its dissolution process.…”
mentioning
confidence: 99%
“…Sn‐substitution brings the added benefit of reducing or removing toxic Pb . The observed stability of the perovskite films is however reduced upon Sn‐substitution as Sn 2+ undergoes rapid oxidation to Sn 4+ , disrupting the perovskite lattice, introducing a self‐doping effect, and creating important carrier recombination centers that decrease the carrier diffusion length, lifetime, and the final device performance . Solutions for this unwanted oxidation have been investigated, with the SnF 2 additive being the most commonly reported stability enhancer, but long‐term solutions are not yet proven …”
mentioning
confidence: 99%